A deep learning approach to depression detection based on Convolutional Neural Networks and Transfer Learning - Sarmi, Kaniz Fatima; Rahman, Shaikh Mahmudur; Sultana, Nusrat Jahan; Anzoom Shanto, Khandaker MD. Asef (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.